Green synthesis of Zinc sulphide (ZnS) nanostructures using S. frutescences plant extract for photocatalytic degradation of dyes and antibiotics - Munyai, Shonisani; Mahlaule-Glory, Louisa M; Hintsho-Mbita, Nomso Charmaine (IOP Publishing, 2022)
Pollutants such as dyes and pharmaceuticals have become a problem in the environment, thus there is a need to find multifunctional materials that are safe and can be used for the removal of various pollutants. In this study, we report on the synthesis of Zinc sulphide (ZnS) nanostructures and their use as photocatalysts for the degradation of dyes and various antibiotics. Fourier transform infrared spectroscopy (FTIR) confirmed the functional groups found in plants and these were linked to the biomolecules identified through Liquid chromatography-mass spectrometry (LCMS). Ultravioletvisible spectroscopy (UV–vis) and x-ray diffraction (XRD) confirmed the formation of the ZnS nanostructures. Thermal Gravimetric Analysis(TGA) and Brunner Emmet Teller(BET) confirmed the material was thermally stable up until 480 °C and mesoporous in nature, respectively. Scanning electron microscope (SEM) and transmission electron microscope (TEM)showed that the material is spherical in shape and energy dispersive spectroscopy (EDS)further corroborated their formation. From the degradation analysis, 90% of the malachite green (MG) dye could be degraded in 60 min at optimum conditions(pH 6, 25 mg and 10 mg l−1) and the holes were responsible for the degradation. Lastly, when tested against antibiotics, the ZnS material managed to degrade both the sulfisoxazole (SSX) and sulfamethoxazole (SMX). These results showed that the ZnS nanoparticles could be used as a multifunctional material for the degradation of various pollutants.
Journal article published in Materials Research Express, Volume 9, Number 1
Keywords: Zinc Sulphide nanoparticles; Dyes; Pharmaceuticals; Green synthesis; Zinc sulfide; Dyes and dyeing -- Chemistry